2015
DOI: 10.1002/cbin.10398
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ and EGF induce the differentiation of human embryo mesenchymal stem cells into epithelial‐like cells

Abstract: The mesenchymal to epithelial transition (MET) occurs in organ development and anti-tumorigenesis. We have investigated the effects of calcium (Ca(2+)) and epidermal growth factor (EGF) on human mesenchymal stem cell (hMSCs) differentiation into epithelial-like cells. hMSCs lost their biological characteristics after EGF transfection, and MET was achieved by adding 0.4 mmol Ca(2+). Western blotting and immunofluorescence showed expression of EGF, keratin, keratin 19 (K19), β1-integrin, E-cadherin and phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…EGF stimulates proliferation of MSCs by binding to EGF receptor (EGFR) [ 38 ]. MSCs transfected with an EGF vector and stimulated by Ca + can differentiate into epithelial-like cells [ 39 ]. FGF, which constitutes a family of at least seven closely related polypeptides with heparin-binding properties, plays a pivotal role during the initial stage of endodermal patterning [ 40 ].…”
Section: Hepatic Differentiation Protocolmentioning
confidence: 99%
“…EGF stimulates proliferation of MSCs by binding to EGF receptor (EGFR) [ 38 ]. MSCs transfected with an EGF vector and stimulated by Ca + can differentiate into epithelial-like cells [ 39 ]. FGF, which constitutes a family of at least seven closely related polypeptides with heparin-binding properties, plays a pivotal role during the initial stage of endodermal patterning [ 40 ].…”
Section: Hepatic Differentiation Protocolmentioning
confidence: 99%
“…The hMSC used in this study were isolated from 4-to 6-week-old embryos from volunteers who underwent pregnancy termination with RU-486, an antiprogesterone compound. 13 Our previous studies 17,18 [6][7][8][9] have demonstrated that MSC therapy could achieve remarkable therapeutic outcomes in SLE patients and animal models. Zhou et al 6 used human bone marrow MSC (BMSC) and Gu et al 7 used mouse-derived MSC to treat SLE in MRL/Lpr mouse models for 33 weeks and found that the survival rate in the treatment groups was 100% versus 40% and 55% in the control groups.…”
Section: Discussionmentioning
confidence: 99%